Influence of suprathermal electrons on ECE measurements in the Uragan-3M torsatron - Pavlichenko, R.O. (Вопросы атомной науки и техники, 2015)
Electron cyclotron emission (ECE) diagnostic (superheterodyne millimeter wave radiometer) is a regular tool to provide the radial distribution and time dependence for a bulk electron population for the Uragan-3M (U-3M) plasmas. Under some plasma conditions when RF heating pulse switched off a substantial increasing of the radiation intensity signal we observed at the frequencies which corresponds to the second and third harmonics of ECE (2ωce ,3ωce) of the extraordinary mode. The existing phenomena could be attributed with the presence of the suprathermal (ST) and / or “runaway” electrons (RE) in U-3M plasmas. A procedure is described by which the electron temperature profile can be obtained from spectral measurements of the cyclotron emission at optically thin frequencies. No absolute calibration of the detection equipment is needed for this method. Диагностика электронного циклотронного излучения (ЭЦИ) является штатным инструментом для обеспечения информации о временной эволюции и радиальном распределении электронной температуры во время экспериментов на торсатроне Ураган-3М (У-3М). Было обнаружено, что после окончания импульса ВЧ-нагрева наблюдается значительное увеличение сигнала интенсивности излучения на частотах, что соответствует второй и третьей гармоникам ЭЦИ (2ωce ,3ωce) необыкновенной волны. Существующие явления можно объяснить присутствием сверхтепловых или «убегающих» электронов (УЭ) в плазме торсатрона У-3М. Описана процедура, в которой профиль температуры электронов может быть получен из спектральных измерений циклотронного излучения для оптически тонких гармоник. Обнаружено, что для этого метода не требуется абсолютной калибровки оборудования. Діагностика електронного циклотронного випромінювання (ЕЦВ) є штатним інструментом для забезпечення інформації про тимчасову еволюцію і радіальний розподіл електронної температури під час експериментів на торсатроні Ураган-3М (У-3М). Було виявлено, що після закінчення імпульсу ВЧ-нагріву спостерігається значне збільшення сигналу інтенсивності випромінювання на частотах, що відповідає другій і третій гармонікам ЕЦВ (2ωce ,3ωce) незвичайної хвилі. Існуючі явища можна пояснити присутністю надтеплових або «тікаючих» електронів (ТЕ) у плазмі торсатрона У-3М. Описана процедура, в якій профіль температури електронів може бути отриманий із спектральних вимірювань циклотронного випромінювання для оптично тонких гармонік. Виявлено, що для цього методу не потрібно абсолютного калібрування обладнання.